Correlation Between Learning Motivation and Problem-Solving Ability Based on Gender - Irham Habibi Harahap (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study is to determine the relationship between students' motivation to learn and their mathematical problem-solving abilities based on their gender. This study employs a quantitative method with a correlation survey approach to assess students' motivation and mathematical problem-solving abilities. It involves 73 students from Madrasah Tsanawiyah. The data analysis technique used in this study was the product-moment correlation test, which yielded a value of 0.001 for sig.(2-tailed). Means 0.001 0.05, Ha is accepted, and H0 is rejected based on male students. The value of sig. (2-tailed) is 0.003, meaning 0.003 0.05, Ha is accepted, and H0 is rejected based on female students. And the value of sig.(2-tailed) is 0.000, meaning 0.000 0.05 then Ha is accepted, and H0 is rejected. There is a significant positive correlation between learning motivation and mathematical problem-solving with a correlation coefficient value of 0.435 then the level of correlation between variables is a moderate correlation. The coefficient of determination test is (0.435)2 x 100% = 18.92%. This means that only 18.92% of the contribution of the independent variable, namely learning motivation, to the dependent variable, is the student's mathematics learning outcomes and other things influence 81.08%.